Biological control of diamondback moth, plutella xylostella (L.),using parasitoids and bacteria: a review - Idris , A. B.; Norhayati Abdul Mukti (Universiti Kebangsaan Malaysia, 1997)
Resistance of diamondback moth (DBM), Plutella xylostela (L), to coventional pesticides and concerns about environmental quality have lead to increased worldwide efforts to develop viable biocontrol methods for DBM. The success of using parasitoids, especially larval parasitoids like Diadegma, Cotesia and Microplitis species for controlling DBM have been reported in several countries. These larval parasitoids of DBM are commonly found in the field. Diadegma semiclausum (=eucerophaga) Hellen is the major parasitoid of DBM in Europe and Asia, while Diadegma insulare (Cresson) are predominates in the Americas. To date, the bacterium, Bacillus thuringiensis Berliner subspecies kurstaki, has been the most widely used DBM pathogen. Although it is environment friendly pesticides, its effectiveness always vary with weather, field location and frequency of application per season. These are the main factors that contribute to the slow acceptance of B.thuringiensis by the cabbage growers worldwide. Because of this many studies have been done to improve its efficacay and persistence in the field. This paper provides an overview of the current status of these agents for use in controlling DBM and suggest research that is needed to improve the usefulness of these biocontrol agents and to maximize their impact on the DBM management in the future